OsCSLD4 confers salt–alkali tolerance by regulating gene expressions in photosynthesis and carbohydrate biosynthesis pathways, cell wall hemicellulose accumulation and physio-biochemical adaptability in rice - Zhijian Liu; Cuili Wu; Wenjie Li; Li Hu; Xingyue Fu; Binhua Hu; Yongxiang Liao; Zufen Xiang; Haibo Jiang; Weizao Huang; Xiaocheng Yang; Anping Du; et al. (Plant Stress)
In rice, cell-wall matrix polysaccharides contribute to salt–alkali tolerance. However, the mechanism by which cell-wall matrix polysaccharides and their biosynthetic genes regulate salt–alkali tolerance in rice remains unclear. To address this question, we report on the regulatory mechanism of salt–alkali tolerance of the 1,4-β-d-xylan synthase gene OsCSLD4 in the hemicellulose biosynthesis pathway. Mutant of OsCSLD4, nd1 and its wild-type were analyzed using comprehensive techniques and methods, including phenotyping, gene expression, comparative transcriptomic analysis, qPCR validation, and determination of physio-biochemical indices. We found that the salt–alkali tolerance of nd1 was lower than that of the wild type, and the expression of the OsCSLD4 gene was induced under salt–alkali stress. Comparative transcriptomic analysis revealed that the expression levels of genes involved in photosynthesis, carbohydrate, and cell wall matrix polysaccharide biosynthesis pathways in nd1 seedlings were downregulated compared to those in the wild type under salt–alkali stress. Accordingly, physio-biochemical analysis demonstrated that nd1 seedlings had reduced levels of chlorophyll, total soluble sugar, starch, and hemicellulose, coupled with a significant increase in malondialdehyde content under salt–alkali stress. In essence, the OsCSLD4 gene confers salt–alkali tolerance to rice by regulating the hemicellulose content to strengthen cell wall integrity and enhance intracellular physio-biochemical salt–alkali tolerance at the cellular level, thereby maintaining photosynthetic capacity and growth at the plant level. This study revealed that OsCSLD4 has potential value in molecular breeding for the development of salt-alkali-tolerant rice varieties.